Static analysis in datalog extensions. - Halevy, Alon Y.
We consider the problems of containment, equivalence, satisfiability and query-reachability for datalog programs with negation. These problems are important for optimizing datalog programs. We show that both query-reachability and satisfiability are decidable for programs with stratified negation provided that negation is applied only to EDB predicates or that all EDB predicates are unary. In the latter case, we show that equivalence is also decidable. The algorithms we present can also be used to push constraints from a given query to the EDB predicates. In showing our decidability results we describe a powerful tool, the query-tree, which is used for several optimization problems for datalog programs. Finally, we show that satisfiability is undecidable for datalog programs with unary IDB predicates, stratified negation and the interpreted predicate ≠.
Keywords: Theory of computation; Logics and meanings of programs; Specifying and Verifying and Reasoning about Programs; Information systems; Database management; Languages; Algorithms; Theory; Verification